Courtney Cummins: capstone - Cummins, Courtney, artist (Colorado State University. Libraries, 2017)
The artist's statement: Most of my artwork reflects my current state of mind. Whether it's through the use of bold colors, or surreal imagery, I seek to transcend the physical world and revitalize a newfound respect for seemingly ordinary subjects or ideas. For me, being an artist is about the experience in itself and the story or perspective that I choose to bring to life. My urge to create drives me to explore how I can play with various mediums to describe my current state of mind. Over recent years, I have realized that my love for creating art cannot be described or contained within one medium only. As I continue to evolve as an artist, I seek to show the beauty in the interplay that goes along with my love for graphic design and other fine art practices such as painting, drawing, or sculpture. My work represents the healing effect that I receive from the creative process, and the rewarding freedom that it gives me to express myself. I am endlessly inspired by the power that art has to bring people together and hope to involve my audience in the rewarding experience that I feel when I create works of art.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design